2011
DOI: 10.5539/ijms.v3n2p73
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Determinants of User Acceptance of Electronic Exchanges (Case Study: Buying and Selling Section of Active Companies of Iran's Textile Industry)

Abstract: Electronic commerce is being increasingly developed as the modern phenomenon of business world. But this fact should be considered that in spite of all benefits electronic commerce brings about, it should not be observed as a purpose. Certainly necessary actions must be taken with regard to accepting of electronic commerce for applying and facilitating of it in the organization. The purpose of this research is designing a comprehensive model for acceptance of electronic exchanges technology in textile industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The use of TAM in implementing e-commerce comes with different strengths and weaknesses, as indicated by various scholars. It is identified that indicators of electronic exchange acceptance are based on the main emphasis of increasing TAM having two extended constructs: quality and Trust [ 180 ]. A research framework is proposed by Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The use of TAM in implementing e-commerce comes with different strengths and weaknesses, as indicated by various scholars. It is identified that indicators of electronic exchange acceptance are based on the main emphasis of increasing TAM having two extended constructs: quality and Trust [ 180 ]. A research framework is proposed by Ref.…”
Section: Discussionmentioning
confidence: 99%